Pengaruh Tari Rapai Geleng dalam Mengembangkan Sosial Anak Usia 5-6 Tahun di RA Safinatul Najjah Manggeng - Zahra, Sri Amalia; Juwita, Rani Puspa (Generasi Emas, 2024)
Improving the social quality of individuals can be achieved through interaction and adaptation of behavior in society according to accepted guidelines. In this case, Rapai Geleng dance is proven as an effective tool to stimulate social growth in early childhood. This study was directed at measuring the impact of Rapai Geleng dance training on social development in children aged 5 to 6 years at RA Safinatul Najjah Manggeng. The focus of the study was on 12 children, divided into 7 girls and 5 boys. The method used is quantitative experimental with a single group testing design before and after the experiment. The study used the whole sample and collected data through observation and documentation. Data analysis used an independent t-test to compare scores before and after the experiment. The results showed a marked improvement in the social skills of the children who engaged in Rapai Geleng dance, with an increase in the mean score from 6.5 to 17.5. Hypothesis testing confirmed the significant difference in scores, resulting in a T count of 7.888 which is greater than the T table of 1.796, with degrees of freedom (df) 11 and a significance value (p-value) of 0.00, which is lower than 0.05. This data reinforces the conclusion that Rapai Geleng dance is effective in supporting children's social development.